The role of the marketing intelligence system in the quality of the insurance service : Applied research in the National Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The current research seeks to identify the role of the marketing intelligence system in its dimensions (customer intelligence, market intelligence, competitor intelligence, insurance product intelligence, sales representatives) and its reflection on improving the quality of the insurance service provided by the National Insurance Company represented in its dimensions (reliability, response, tangibility, Safety, the spirit of empathy, communication) adopted in the current research, and based on that, the research came as an attempt to find out the extent to which the research sample company can apply the approach of the marketing intelligence system and its impact on improving the quality of the insurance service provided to customers, The problem of the research was the absence of an organizational unit that undertakes the tasks of applying the marketing intelligence system approach affiliated to the marketing department in the company in question. The researcher should apply this system in the company under study because of its impact on improving the quality of the insurance service provided to the public